2017
DOI: 10.1177/0022034517700131
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among Bone Quality, Implant Osseointegration, and Wnt Signaling

Abstract: A variety of clinical classification schemes have been proposed as a means to identify sites in the oral cavity where implant osseointegration is likely to be successful. Most schemes are based on structural characteristics of the bone, for example, the relative proportion of densely compact, homogenous (type I) bone versus more trabeculated, cancellous (type III) bone. None of these schemes, however, consider potential biological characteristics of the bone. Here, we employed multiscale analyses to identify a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 30 publications
1
67
0
2
Order By: Relevance
“…Based on one study, 26 19,28,29 However, in contrast to this study, the results from those studies were based on products from different companies. The probability of failure was significantly higher in the mandibular anterior area than in the other sites.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Based on one study, 26 19,28,29 However, in contrast to this study, the results from those studies were based on products from different companies. The probability of failure was significantly higher in the mandibular anterior area than in the other sites.…”
Section: Discussionmentioning
confidence: 84%
“…The probability of failure was significantly higher in the mandibular anterior area than in the other sites. Based on one study, 26 being a risk factor. Many authors have reported that the probability of implant failure is highest for maxillary anterior teeth.…”
Section: Discussionmentioning
confidence: 99%
“…We located the sites where osteoprogenitor cells resided. Type III bone is penetrated by vascular sinusoids (Figure I) and co‐immunostaining with DAPI, Osterix, and beta galactosidase to identify Wnt responsive cells identified this as the primary location for this osteoprogenitor cell population (Figure J). By POD7, these Runx2 +ve and Osterix +ve cells had contributed to the faster healing observed in Type III bone osteotomies (Figure K‐M).…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, we demonstrated that the murine maxillary edentulous ridge represents dense, lamellar Type I bone and a healed maxillary M1 extraction site represents trabecular Type III bone. 27 Therefore, using a constant drill speed, we tested whether osteotomy healing differed between these two Types of bone.…”
Section: Type III Bones Heal Faster Than Type I Bonesmentioning
confidence: 99%
“…This slow increase in secondary stability could be explained by the fact that implants were inserted in atrophic ridges (mean bone width 3.8 mm), with most of the implant surface facing only buccal and lingual cortical bone. Recent histomorphometric and biomolecular studies clearly demonstrated that new bone formation starts primarily in the spongious bone and that the rate of new bone formation is significantly increased in trabeculated cancellous bone osteotomies compared to equivalent osteotomies in densely compact cortical bone [ 36 ]. These considerations could explain why, in the present study, ISQ values at T2 resulted significantly higher in maxilla than in mandible and suggest that the healing period after wedge implant placement in narrow ridges could be slightly longer than that of a standard implant inserted in a bone crest with a good quantity of spongious bone.…”
Section: Discussionmentioning
confidence: 99%